Biodiesel-based biorefineries: hierarchical design and implementation - Ahmad Farid, Mohammed Abdillah; Zakaria, Mohd Rafein; Ramli, Irmawati; Yunus, Robiah; Hassan, Mohd Ali (Elsevier, 2023)
Since the demand has been increasing over the years, the long-term sustainability of biodiesel production should be taken into consideration. The fact that major biodiesel feedstocks conflict with food security makes the situation more pressing. To meet these challenges, measures must be taken by pursuing the integral use of biomass to allow the development of multiple products along with biodiesel through biorefineries. A step-by-step biorefinery design strategy is discussed to ensure achieving the highest level of sustainability, economic viability, and environmental friendliness over a stand-alone production system. Of the few approaches presented in the literature, a hierarchal methodology is proposed. The term hierarchy refers to the chronological stages of raw materials decomposition into different building blocks, then into various products through a series of processes. Here, the discussion begins with an introduction to biodiesel, types of feedstock, and production technologies. The feedstocks used in biodiesel production are selected for their oil quality and economics, and their availability, opportunity, and limitations are reviewed herein. The evaluation of the hierarchical design for biodiesel-based biorefineries is also scrutinized by addressing the use of all raw materials available at the production plants to manufacture a range of potential value-added products. The economic feasibility and environmental impacts of biodiesel biorefineries are also presented.